Age-Related Benefits of Digital Noise Reduction for Short-Term Word Learning in Children With Hearing Loss. - Pittman, Andrea (Journal of Speech, Language & Hearing Research, 2011)
Purpose: To determine the rate of word learning for children with hearing loss (HL) in quiet and in noise compared to normal-hearing (NH) peers. The effects of digital noise reduction (DNR) were examined for children with HL. Reprinted by permission of the publisher.